2007
DOI: 10.1093/carcin/bgl241
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive anti-inflammatory activities of curcumin and other phytochemicals mediated by MAP kinase phosphatase-5 in prostate cells

Abstract: As inflammation emerges as a risk factor for prostate cancer (PCa), there is potential for chemoprevention by anti-inflammatory agents. Dietary phytochemicals have been shown to have chemopreventive properties which may include anti-inflammatory activities. In this study, we demonstrate a role for mitogen-activated protein kinase phosphatase-5 (MKP5) in mediating anti-inflammatory activities of the phytochemicals curcumin, resveratrol and [6]-gingerol. We utilized the cytokines tumor necrosis factor-alpha (TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(86 citation statements)
references
References 43 publications
1
85
0
Order By: Relevance
“…Numerous polyphenolic phytochemicals such as resveratrol, curcumin, flavonoids, epigallocatechin gallate, and chalcones have been well studied and reported to interfere with specific stages of the carcinogenic process. [24][25][26][27] In our previous results, we observed that introduction of hydroxyl group on phenyl moiety increased bioa These authors contributed equally to this work. …”
Section: -23mentioning
confidence: 93%
“…Numerous polyphenolic phytochemicals such as resveratrol, curcumin, flavonoids, epigallocatechin gallate, and chalcones have been well studied and reported to interfere with specific stages of the carcinogenic process. [24][25][26][27] In our previous results, we observed that introduction of hydroxyl group on phenyl moiety increased bioa These authors contributed equally to this work. …”
Section: -23mentioning
confidence: 93%
“…Similarly, in a recent study of fermented ginseng, another compound of Chinese medicine associated with anti-inflammatory effects, inhibition of NF-κB activity was detected (Yuan and Chung, 2010). Anti-tumor agents have also been shown to induce apoptosis by modulating NF-κB expression and activity (Pandey et al, 2007), Thus, strategies to inhibit NF-κB may provide a cancer therapy applicable to many types of carcinomas Zheng et al, 2007;Paule et al, 2007;Nonn et al, 2007). In this study, SN suppressed NF-κB activity and PGE2 production in a dose-dependent manner.…”
mentioning
confidence: 61%
“…MKP-5 gene expression may be elevated as a negative feedback mechanism to counteract ERK activation. Importantly, data suggested that anti-inflammation activity by vitamin D and curcumin is mediated by MKP-5, which is a potential mechanism for prostate cancer prevention (20,21). In the mouse model of colon cancer, which was induced by azoxymethane and dextran sulfate sodium, ERK phosphorylation was significantly increased by about 10-fold (22).…”
Section: Discussionmentioning
confidence: 99%